Cold-induced cutaneous vasoconstriction in humans: Function, dysfunction and the distinctly counterproductive - Alba, B. K.; Castellani, J. W.; Charkoudian, N. (Experimental Physiology, 2019)
In humans, cold-induced peripheral vasoconstriction is an essential element of body temperature regulation. Given that the thermoregulatory system responds rapidly to changes in skin temperature, sympathetically mediated cutaneous vasoconstriction represents a crucial 'first line of defense' against excessive reduction in body temperature. Sympathetic noradrenergic vasoconstrictor nerves cause a rapid decrease in skin blood flow, thus increasing the insulative capacity of the skin and decreasing heat loss from the body. Small changes in the activity of these nerves are also responsible for the subtle changes in skin blood flow that occur with normal daily activities or minor changes in environmental temperature. With ageing, hypertension and other conditions, the cutaneous reflex vasoconstrictor response can become excessive or insufficient. Healthy older adults have impaired reflex vasoconstriction, which may result in an impaired ability to defend body temperature in some circumstances. Hypertension is associated with augmented vasoconstriction, which could have pathological implications for left ventricular afterload in individuals already at risk for cardiovascular events. Finally, in some cases, the reflex vasoconstrictor response becomes distinctly counterproductive to its own goals of maintaining cardiovascular and thermoregulatory homeostasis. Examples include Raynaud's phenomenon, in which exaggerated vasoconstriction can produce ischaemia in the periphery, and the cutaneous vasoconstrictor response to therapeutic body cooling in severe hyperthermia, which can limit the heat exchange necessary to prevent serious heat illness.